Convocation-96 and graduate employability / Enabella Tasha Dennis - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Kajian Pengesanan Graduan is an annual study carried out by the Ministry of Higher Education (KPT) to find out the status of graduates after completing their studies. Furthermore, the objective of this research is to gather input from UiTM alumni regarding their experiences with study programs, facilities and services offered by the university. The outcomes of this investigation can assist UiTM in enhancing their efforts to improve graduate employability in accordance with the Ministry of Higher Education's Graduate Employability Strategic Plan 2021-2025. This plan aims to cultivate well-rounded graduates with global employability qualities.